Bilateral Stromal Corneal Dystrophy Mimicking Central Visual Pathway Dysfunction: A Case Report - Imania; El Emir, Newi (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2025)
Progressive bilateral visual loss is a clinical red flag that frequently prompts evaluation for intracranial lesions involving the optic nerves, chiasm, or retrochiasmal pathways. However, anterior segment disorders such as corneal dystrophies may mimic central visual pathway pathology, especially when visual acuity loss occurs without overt ocular pain or inflammation. We report the case of a 31-year-old male presenting with progressive, symmetric visual impairment initially suspected to be neurologic in origin. Slit-lamp examination revealed bilateral mid-stromal crystalline opacities consistent with stromal corneal dystrophy. The absence of afferent pupillary defects, normal fundus findings, and lack of neurologic signs further supported a corneal etiology. This case illustrates the diagnostic challenge of distinguishing anterior segment disease from true neuro-ophthalmologic conditions. Failure to recognize corneal dystrophy may result in unnecessary neuroimaging and delayed treatment. Clinicians assessing bilateral vision loss, particularly in young adults, must include detailed anterior segment evaluation in their diagnostic algorithm to prevent mislocalization of pathology and ensure accurate management. Keyword: Cornea, corneal dystrophy, bilateral visual loss, neuro-ophthalmology, keratoplasty